The Effect of Tax Wedge and Industrialization on Female Labor Force Participation - Aydın, Fatma Fehime; Levent, Cemalettin (International Journal of Contemporary Economics and Administrative Sciences, 2022)
The participation of women in the workforce is a factor that has very important socio-economic effects, especially on economic growth and development. Therefore, it is important to determine the factors affecting female labor force participation (FLFP) and thus to implement policies to increase FLFP. In the study, 17 OECD member countries were selected and the effects of tax wedge and industrialization on FLFP were examined based on the data of these countries for the period 2000-2019. It has been determined that industrialization generally affects FLFP positively, but the tax wedge has an effect on FLFP in a limited number of countries. In addition, while it is seen that both the tax wedge and industrialization are effective in the long term, it has been determined that only industrialization is effective in the short term and the tax wedge has no effect.